Peran Komite Madrasah Dalam Meningkatkan Mutu Pendidikan di MI DDI Nurul Islam Timika Papua - Zunaida, Laily; Huggy Nur hikmah Pratiwi (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2022)
The idea of involving the community in the concept of the Madrasah Committee is an initiative in the context of advancing Madrasah, so that there is no perception that madrasah committee as the representative of parents and the community only gives a material contibution. Therefore, to carry out its roles and functions in achieving the quality of education, the madrasah committee must develop plans or programs in order to realize the goals that have been planned with madrasah. This study aimed at describing the quality of education at MI DDI NURUL ISLAM Timika Papua, finding out the role of the madrasah committee in improving the quality of education at MI DDI NURUL ISLAM Timika Papua and also finding out what are the supporting and inhibiting factors for the madrasah committee in improving the quality of education at MI DDI NURUL Islam Timika Papua. The method used in this research is qualitative method with case sudy approach. The result of the research is that the madrasah committee has carried out its roles as Advisory Agency, Supporting Agency, Controlling Agency, and as Mediator (Executive). The Madrasah committe as Mediator (Executive) between the madrasah and the community is the most optimal role. This is due to the shared responsibility between the madrasah and the community as partners in building education. The supporting factors are the similarity in both vision and missions of the madrasah and the togetherness in planning programs of madrasah to improve the quality of education. Meanwhile, the obstacle is that madrasah committee has limited time due to busyness and this is the cause of the lack of coordination between the madrasah and the madrasah committee.